Witches' Milk: Queer Breastfeeding and Alternative Kin-Making in Isak Dinesen's "The Caryatids". Issue 4 (2nd October 2022) - Mortensen, Peter
ABSTRACT: In this essay, I use the recent convergence of queer, feminist, and ecocritical perspectives under the heading of "queer ecology" to analyse how Danish bilingual author Isak Dinesen (real name: Karen Blixen) deploys breastfeeding in her Gothic story "The Caryatids: An Unfinished Story." Queer ecology entails critiquing the assumption (or myth) that heterosexual identities, monogamous relationships, consanguineous kinship networks, and reproductive nuclear families are better, healthier, or more "natural" than other formations. I situate Dinesen in opposition to the tradition of Enlightenment "lactivism, " whose proponents (chief among them Jean-Jacques Rousseau) celebrated exclusive maternal breastfeeding within hetero-reproductive nuclear family structures. In my reading of "The Caryatids, " I place special emphasis on three Gothic-related female characters—the incestuous wife, the adulterous mother, and the "gypsy" witch—who breastfeed queerly, knowingly or unknowingly thwarting the demand that women nurse the monogamous and patriarchal bio-family order into existence. When removed from its sanctioned familial context, I argue, the lactating breast in Dinesen's narrative proves a disorderly signifier of errancy and dissent, pointing towards the possibility of alternative, emergent, contingent, and potentially more sustainable configurations of gender, relationship, and community.